HUBUNGAN KEAKTIFAN PENGURUS ORGANISASI SISWA INTRA SEKOLAH (OSIS) DALAM PELAKSANAAN KEGIATAN ORGANISASI SISWA INTRA SEKOLAH (OSIS) DENGAN HASIL BELAJAR PADA MATA PELAJARAN SEJARAH DI SMAN 1 SINGKEP - A Fathisra Alawiya A; Isjoni Isjoni; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: SMAN 1 Singkep officially established on January 1, 1969 with sk Mendikbud 28 May 1969 Number 83/UKK/3/1969. This research aims (1) to find out the work program created by the administrator of Sma Negeri 1 Singkep, (2) To know the activeness of the student council in carrying out the student council activities in SMAN 1 Singkep, (3) To know the results of studying student council in historical subjects in SMAN 1 Singkep, (4) To know the activeness of the Student Council Administrator in the Implementation of Student Council Activities With The Results of Learning On Historical Subjects in SMAN 1 Singkep. The research approach used in this study is quantitative research by survey method, using simple linear regression analysis. The subject of this study was the student council of SMAN 1 Singkep which numbered 40 students. The criterion of the degree of coefficient relationship is 0. 153,meaning the activeness of the student council in the implementation of student council activities has a low relationship due to what is the value of pearson corelation 0.21-0.40. The higher the activeness of student council administrators in the implementation of student council activities,the higher the learning results of students in SMAN 1 Singkep. Based on a simple linear regression analysis known as a positive value regression coeffesien with the regression equation Y = 67.786 + 0.477X, meaning the activeness of the student council in the implementation of student council activities (X) has a positive effect on the study results (Y). The value of t count = 2.624 > 0.3120 = t table, so itcan be concluded that H0 is rejected, which means that "There is an Effect of Student Council Administration Activity in the Implementation of Student Council Activities (X) on Learning Outcomes (Y)". The R square value of 0.153 indicates that the contribution of the student council's activeness variable in the implementation of student council activities (X) to the learning outcome variable (Y) is 15.3%. While the remaining 84.7% is the influence of other variables that are not studied.Key Words : Relationship of Active Student Council Management in the Implementation ofStudent Council Activities With Learning Results in SMAN 1 Singkep